2017
DOI: 10.1016/j.matpur.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Toric chordality

Abstract: We study the geometric change of Chow cohomology classes in projective toric varieties under the Weil-McMullen dual of the intersection product with a Lefschetz element. Based on this, we introduce toric chordality, a generalization of graph chordality to higher skeleta of simplicial complexes with a coordinatization over characteristic 0, leading us to a far-reaching generalization of Kalai's work on applications of rigidity of frameworks to polytope theory. In contrast to "homological" chordality, the notion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…The following recent result of Adiprasito [Adi15] generalizes the lower bound theorem, and will be crucial in our proof of Conjecture 1.1(i).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The following recent result of Adiprasito [Adi15] generalizes the lower bound theorem, and will be crucial in our proof of Conjecture 1.1(i).…”
mentioning
confidence: 83%
“…In [ANS15] we provided a notion of higher chordality of simplicial complexes and showed that it generalizes the classical notion of chordal graphs. In [Adi15] the first named author introduced toric chordality, a powerful algebraic tool to study chordality in the stress-space of the simplicial complex as studied by Lee [Lee96]. He related this algebraic notion of chordality to the higher chordality notions of [ANS15] and derived, among many other results, a quantitative version of the GLBC in terms of the topological Betti numbers of induced subcomplexes.…”
Section: Introductionmentioning
confidence: 99%
“…This almost is a Lefschetz-type result that characterizes primitive Betti numbers, compare also [Sta96]. We refer to [Adi15] for related applications towards a quantitative lower bound theorem, and also Remark 5.18 for a small application. and further developed in [AB12].…”
Section: Corollary 425 Let ∆ Be a Simplicial Ball And Assume That ∂mentioning
confidence: 65%
“…Here ∂∆ i denotes the boundary of an i-simplex and C k is the boundary of a k-gon. 1 In the following two lemmas we compute the τ -vectors of these two minimal cases.…”
Section: Nearly Stacked Spheresmentioning
confidence: 99%
“…Put differently, τ i is the weighted average of the i-th reduced Betti number of all induced subcomplexes C[W ], with respect to weights that are uniform on subsets W ⊆ V of equal size and add up to 1 |V |+1 for each size j ∈ {0, . .…”
Section: Introductionmentioning
confidence: 99%